Intravascular large B-cell lymphoma confirmed by lung biopsy - Liu, Chunli (e-Century Publishing Corporation, 2014)
Intravascular lymphoma is a very rare form of large B-cell non-Hodgkin’s lymphoma which is characterized by selective growth of lymphoma cells within the lumina of small blood vessels. We report a 64-year-old woman visited hospital because of persistent cough, intermittent high fever as high as 38.7°C and occasional shortness of breath. Her chest CT showed left upper lobe pneumonia and tuberculosis skin test (PPD test) was positive. She was suspected with tuberculosis and treated with anti-tuberculosis drugs. However, her symptoms and general condition deteriorated, and she visited our hospital. She had no abnormal findings on physical examination, but had abnormal laboratory findings, including decreased hemoglobin, elevated LDH and C-reactive protein. Arterial blood gas analysis showed moderate hypoxaemia. A chest radiograph showed pneumonia in whole lung and CT showed diffused ground glass opacities in both lung fields. Lung biopsy confirmed a diagnosis of intravascular large B-cell lymphoma. Primary pulmonary manifestation is very rare. The diagnosis is based on the histopathology and immunohistochemistry.